2008
DOI: 10.1093/occmed/kqm148
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathological features of a patient population of targets of workplace bullying

Abstract: Workplace bullying can have severe mental health repercussions, triggering serious and persistent underlying disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 22 publications
3
61
0
5
Order By: Relevance
“…A third Norwegian study, conducted among nurse assistants, however, only found an effect of violence and threats, but not of workplace bullying (11). In France, a small-scale follow-up study of targets of workplace bullying showed high levels of psychopathological symptoms that persisted for at least 12 months (14).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…A third Norwegian study, conducted among nurse assistants, however, only found an effect of violence and threats, but not of workplace bullying (11). In France, a small-scale follow-up study of targets of workplace bullying showed high levels of psychopathological symptoms that persisted for at least 12 months (14).…”
Section: Discussionmentioning
confidence: 94%
“…In 2003, Kivimäki et al (15) showed that prolonged bullying predicted self-reported physiciandiagnosed depression after two years of follow-up with an adjusted OR of 4.81 in a cohort of Finnish hospital workers. Other prospective studies have investigated the effect of workplace bullying on psychological distress, a concept that likely shares common characteristics with caseness of MDE (11)(12)(13)(14). Two Norwegian studies found a prospective association between workplace bullying and onset of psychological distress in the general workforce (12,13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Divincova & Sivakova (2014), the most frequent factors that could lead to mobbing are: superiority of the mobber, selfishness, personal issues often stemming from problems at home, complexes, jealousness, mutual dislike, achievement of career growth and psychological terror at the expense of another. Brousse et al (2008) tested Leymann's Inventory of Psychological Terror criteria for bullying as an indicator and showed that 81 % of patients showed high levels of perceived stress at work. Sutton (2010) additionally explains that different attacks, such as personal insults and status attacks cause degradation of the victim's social position and pride in the form of status degradation.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Otros estudios 61,62 indican que pueden diferenciarse dos grupos: un primer grupo (en torno al 70%) que muestra características de normalidad y un segundo grupo con variedad de perfiles, fundamentalmente del espectro neurótico. Hay investigaciones [62][63][64][65][66][67] que han administrado el MMPI-2 (Minnesota Multiphasic Personality Inventory) entre afectados y muestran perfiles de trastorno de la personalidad más altos en víctimas que entre la población general, principalmente en lo que respecta al espectro neurótico y la somatización, así como altos niveles de ansiedad social en las relaciones interpersonales, entre otros rasgos, pero no suficientemente del perfil paranoide para establecer una asociación generalizada. Por ejemplo, en una investigación reciente 65 González Trijueque y Delgado Marina compararon una muestra de 50 víctimas de APT con otra de trabajadores activos que actuaron como control.…”
Section: Tabla 2 Fases Del Mobbing Según Diferentes Autoresunclassified